The effects of pictures on the order of accessing online war stories - Normah Mustaffa, -; Faridah Ibrahim, -; Mus Chairil Samani, - (Universiti Kebangsaan Malaysian, 2009)
Research on how people read news stories has shown that readers chose to read and access news stories associated with pictures that contained an element of attraction. Researchers have found that the emotional elements within the picture could also play a role. It is unclear how neutral human interest pictures influence readers to access news stories. Is the access process influenced by less emotive pictures or more human interest elements? These issues were explored in an experiment in which 24 students participated. The experiment compared similar news that was accompanied with a human interest picture, information graphic and without information graphic. The focus of the news stories was on war news which almost always contained human interest elements that could be neutral or emotion-laden. The experiment suggested that human interest pictures of war stories could be equally effective in attracting readers to read and remember the news stories.